2011
DOI: 10.1136/jcp.2010.087627
|View full text |Cite
|
Sign up to set email alerts
|

The reference interval of thyroid-stimulating hormone in Hong Kong Chinese

Abstract: The authors have set up the reference interval of TSH for the local population, and their findings also suggest that the importance of excluding subjects with thyroid antibodies in the reference population should not be overemphasised. Moreover, the international authorities should consider recommending percentile-equivalent action limits instead of an absolute cut-off on TSH for categorisation of different types of thyroid dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…The absolute concentrations of these antibodies were not compared in any of these papers. As to some antibodies, mostly in lithium-naive patients, we found higher concentration in female than in male subjects what may correspond to the results of Chan et al [5] obtained in the general population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The absolute concentrations of these antibodies were not compared in any of these papers. As to some antibodies, mostly in lithium-naive patients, we found higher concentration in female than in male subjects what may correspond to the results of Chan et al [5] obtained in the general population.…”
Section: Discussionsupporting
confidence: 91%
“…A gender effect on the thyroid antibodies was found in the general population. Chan et al [5] showed that the concentrations of TPOAb > 5.61 IU/mL and of antibodies against thyroglobulin (TGAb) > 4.11 IU/mL were more than twice as frequent in female than in male subjects.…”
Section: Introductionmentioning
confidence: 99%
“…When persons who are thyroid antibody‐positive are excluded, the reference interval for TSH invariably falls . Addition of ultrasonography appears to add little in identifying persons with occult thyroid disease …”
Section: Discussionmentioning
confidence: 99%
“…The upper limit of TSH was lowered to 3.6–3.7 mU/L [3, 15]. It was believed that the skewing right tail of the TSH distribution curve was caused by the inclusion of those with occult thyroid dysfunctions most representatively as HT.…”
Section: Discussionmentioning
confidence: 99%